Electronic appeals in a developing digital state: the experience of the Russian Federation and the Republic of Belarus - Andrichenko, Lyudmila V; Plyugina, Inna V.; Gaunova , Zhanna A.; Kandratovich Natallia М.; Kisialiova Tatsiana М. (Journal of the Belarusian State University. Law, 2020)
The development of information technologies has had an impact on all spheres of public life, including interaction between the state and the public. The form of such interaction is electronic appeals, which have received recognition and consolidation in various countries of the world, including the Russian Federation and the Republic of Belarus. However, the legislation on electronic communications in these countries does not fully take into account the needs of modern society and does not take into account all current trends. The emergence of new forms of communication determines the need for a new look at the content of electronic appeals, identifying their features, determining the order of their direction and consideration. This article analyzes the issues of legal regulation of the issues of sending and reviewing electronic appeals in the Russian Federation and in the Republic of Belarus, and offers suggestions for further development of the legal framework in this area.